Sociological Implications of Sentencing Disparities in Corruption Verdicts: A Case Study in Yogyakarta - Kurniawan, Dika (Sahabat Akademia Group, 2025)
This study investigates the sociological implications of corruption court decisions on local communities in Yogyakarta. While most previous research on corruption verdicts has focused on normative-legal aspects, this article addresses the gap by exploring how disparities in sentencing affect perceptions of justice, social trust, and anti-corruption norms. A qualitative case study approach was employed, analyzing two corruption verdicts (Decision No. 9/Pid.Sus-TPK/2024/PN Yyk and Decision No. 1/Pid.Sus-TPK/2022/PN Yyk). Data was collected through in-depth interviews with community leaders, legal sociologists, and journalists, as well as document analysis and participant observation. Thematic analysis was applied to identify recurring patterns in community responses and perceptions. The study reveals that sentencing disparities undermine public trust in judicial institutions, fostering perceptions of “selective justice.” Communities interpret verdicts not only as legal outcomes but also as symbolic messages about social norms. Light sentences are perceived as legitimizing corruption and eroding collective morality, while consistent and firm verdicts strengthen anti-corruption awareness. The findings highlight that court decisions play a dual role as both legal enforcement and social communication, directly shaping community engagement in combating corruption. The research is context-specific, focusing on Yogyakarta, and thus the findings may not fully generalize to other regions. However, it underscores the need for policymakers and judges to consider the broader sociological impact of verdicts to rebuild public trust and strengthen social resilience against corruption.